Interações discursivas e indicadores de habilidades cognitiva sem atividades experimentais investigativas de ensino e aprendizagem em um clube de ciências - COELHO, Antonia Ediele de Freitas (Universidade Federal do Pará, 2022)
The investigation teaching has been used by several teachers as a didactic-methodological strategy that aims to achieve, in addition to more effective participation of students, greater development of the teaching and learning process in several areas of education, especially in science teaching. Thus, active teaching methodologies that use practical activities associated with manipulative actions, such as Investigative Teaching Sequences (ITS) can provide moments of Discursive Interactions (DI), in which scientific knowledge can be characterized in more evident ways. Thus, this study analyzed how the forms of DI that take place during an SEI, about concepts involving the problem of sound, cooperate with the emergence of Indicators of Cognitive Skills (ICS) in eight students participating in the Science Club “Prof. Dr. Cristovam W. P. Diniz”. We characterized this research as qualitative, using micro genetic analysis to interpret the verbalized DIs perceived in the relationships established between the monitors and the students participating in the Science Club. We tried to identify these ICS in writings and drawings produced by these students, besides elaborating and characterizing an SEI composed of five stages, having as support the concluded research and the experience of the author during the years of performance as a monitory teacher of this space. For data triangulation, we used videotaping, observation, and analysis of written and/or drawn records. The Science Club is considered a non-formal educational environment for teaching, research, and extension of didactic actions focused on Science and Mathematics in fifth and sixth-grade classes of elementary school. With the analyses performed, we identified that the skills developed by the students during the DI are continuously related to the desired proposal, and it was possible to notice ICS based, above all, on the organization, exposition, and explanation of ideas. On some occasions, we evidenced the concentration of mental resources, identification, and analysis of the hypotheses, besides the justification of the results. The generalization of the problem was also evidenced in some episodes. These ICS occur on occasions simultaneous to the IDs that express, mainly, requesting information, providing clues, mirroring, problematizing, and restructuring.